Framing the Land: Canadian Landscapes Revisited in Jin-me Yoon and Lorraine Gilbert’s Photography - Gwendolyne Cressman (Sillages Critiques)
The representation of landscapes through survey photography in the mid to late 1800s largely contributed to document Canadian and American expansionist endeavors, to ascertain the documentary and scientific role that photography would play in that expansion and to foster a sense of national belonging and of Anglo-Saxon supremacy which would also find its expression in landscape painting. While the photographers engaged in geographical and topographical expeditionary missions envisioned the land as the epitome of the sublime landscape, the Group of Seven painters of the 1920s and 1930s later sought to express the essence of Canada’s northern identity through the celebration of a mythical wilderness. This manner of framing the land implied that what was kept outside of the frame or conversely included within its bounds, was often informed by hierarchical relations and colonialist visions of the land. I will be looking at the ways in which two contemporary Canadian photographers, Jin-me Yoon and Lorraine Gilbert, have revisited earlier landscapes in their works and how, through various processes of reframing, they reveal and contest the political, social and ecological underpinnings active in the production of these spaces. I will be paying attention to the critical visual investigation they deploy around Nordic landscapes defined not as the abstract spaces of the nation but as the places where issues of identity and memory unfold.